Quantitative analysis of receptor-mediated uptake and pro-apoptotic activity of mistletoe lectin-1 by high content imaging - N. Beztsinna (Nature Portfolio, 2018)
Abstract Ribosome inactivating proteins (RIPs) are highly potent cytotoxins that have potential as anticancer therapeutics. Mistletoe lectin 1 (ML1) is a heterodimeric cytotoxic protein isolated from European Mistletoe and belongs to RIP class II. The aim of this project was to systematically study ML1 cell binding, endocytosis pathway(s), subcellular processing and apoptosis activation. For this purpose, state of the art cell imaging equipment and automated image analysis algorithms were used. ML1 displayed very fast binding to sugar residues on the membrane and energy-dependent uptake in CT26 cells. The co-staining with specific antibodies and uptake blocking experiments revealed involvement of both clathrin-dependent and -independent pathways in ML1 endocytosis. Co-localization studies demonstrated the toxin transport from early endocytic vesicles to Golgi network; a retrograde road to the endoplasmic reticulum. The pro-apoptotic and antiproliferative activity of ML1 were shown in time lapse movies and subsequently quantified. ML1 cytotoxicity was less affected in multidrug resistant tumor cell line 4T1 in contrast to commonly used chemotherapeutic drug (ML1 resistance index 6.9 vs 13.4 for doxorubicin; IC50: ML1 1.4 ng/ml vs doxorubicin 24000 ng/ml). This opens new opportunities for the use of ML1 as an alternative treatment in multidrug resistant cancers.